2007
DOI: 10.1063/1.2753096
|View full text |Cite
|
Sign up to set email alerts
|

Defect reduction in GaN epilayers grown by metal-organic chemical vapor deposition with in situ SiNx nanonetwork

Abstract: Line and point defect reductions in thin GaN epilayers with single and double in situ SiN x nanonetworks on sapphire substrates grown by metal-organic chemical vapor deposition were studied by deep-level transient spectroscopy ͑DLTS͒, augmented by x-ray diffraction ͑XRD͒, and low temperature photoluminescence ͑PL͒. All samples measured by DLTS in the temperature range from 80 to 400 K exhibited trap A ͑peak at ϳ325 K͒ with an activation energy of 0.55-0.58 eV, and trap B ͑peak at ϳ155 K͒ with an activation ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…3(b), indicating a TD density of 4.7 Â 10 7 cm À2 . The result is comparable with the result of traditional ELOG [14,15]. The decreasing of the TDs related EPD indicates the effect of the PSS to the improvement of crystalline quality.…”
supporting
confidence: 92%
“…3(b), indicating a TD density of 4.7 Â 10 7 cm À2 . The result is comparable with the result of traditional ELOG [14,15]. The decreasing of the TDs related EPD indicates the effect of the PSS to the improvement of crystalline quality.…”
supporting
confidence: 92%
“…Their x-ray diffraction (XRD) characterization showed that in situ SiN x capping prevented the AlGaN layer from relaxing by forming TDs, which have been known to act as recombination centers in GaN. 23 Sample C exhibited the highest near-band-edge luminescence, a result also observed by Xie et al 24 Indeed, as some of the traps in the material would inevitably be near the surface, one could reasonably expect in situ SiN x to reduce the interface state density as well. The increased slope of the CV characteristics in Fig.…”
Section: Resultssupporting
confidence: 61%
“…Therefore, dielectric mask material produced by ex situ deposition and etching procedures [77] or in situ spontaneous etching [78] can be used for ELO GaN and low Al-molar fraction AlGaN. Figure 6 shows a cross-sectional transmission electron microscopy (TEM) image of an ELO GaN sample on sapphire substrate with in-situ nanoporous SiNx mask [79].…”
Section: Epitaxial Lateral Overgrowth Of Aln and High Al-molar Fractimentioning
confidence: 99%